2020
DOI: 10.5812/jjcmb.110136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Concentrations of Fructose on the Expression of TGF-β and α-SMA Genes in Human Hepatic Stellate Cells

Abstract: Background: Liver fibrosis is a reversible response to wound-healing that occurs in most forms of chronic liver damage, beginning with the activation of hepatic stellate cells (HSCs). The increased expression of genes, such as beta-converting growth factor (TGF-β) and actin-alpha smooth muscle (α-SMA) indicates the activation of HSCs. During liver damage, HSCs are activated and converted to myofibroblasts. As a result, the expression of TGF-β and αSMA genes in HSCs increases and leads to liver fibrosis. High f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This could be attributed to the activation of hepatic stellate cells by carbohydrates. Recent studies suggest that high carbohydrate intake directly activates these cells 53 55 , which play a crucial role in the development and progression of liver cirrhosis 56 . An in vitro study by Piras et al demonstrated that conditioned medium derived from hepatocytes treated with a combination of palmitate and fructose elicited a significantly greater degree of transcriptomic changes in hepatic stellate cells than conditioned medium from hepatocytes treated with palmitate alone 57 .…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the activation of hepatic stellate cells by carbohydrates. Recent studies suggest that high carbohydrate intake directly activates these cells 53 55 , which play a crucial role in the development and progression of liver cirrhosis 56 . An in vitro study by Piras et al demonstrated that conditioned medium derived from hepatocytes treated with a combination of palmitate and fructose elicited a significantly greater degree of transcriptomic changes in hepatic stellate cells than conditioned medium from hepatocytes treated with palmitate alone 57 .…”
Section: Discussionmentioning
confidence: 99%